The dating and hookup social scripts of homosexual men. - Quirao, Roevel Paul D.
Two common forms of sexual partnering are dating and hooking up. Past research has focused more on heterosexual sexual partnering and limited attention has been given to homosexual in their dating and hooking up behaviors. This study examines the dating and hookup scripts of seventeen homosexual male respondents and aims to know through interviews how these are different from heterosexual scripts. The researcher categorized their responses into three scripts: cultural scripts, interpersonal scripts and intraphysic scripts. Results indicate that there is little difference betwen heterosexual and homosexual sexual partnering. The difference lies in the secretive nature of their dates while there are no difference for their hooking up. The distinction between hooking up and dating still lies in the presence and motivations of sexual intercourse.